Theoretical Perspectives on Economic Cooperation - Gabriel Ciprian Andruseac; Gabriel Iulian Hertug (CES Working Papers, 2015)
Economic cooperation, the engine of relations of international economic cooperation, is an insufficiently defined, dynamic concept. The transformations of the international environment, globalization and the intensification of economic interdependencies render economic cooperation a must, and not just an option within international relations. Similar to the international environment, economic cooperation undergoes a process of redefinition, of adjustment to the new realities. This article aims at identifying and analyzing the approaches of economic cooperation in this context.
Keywords: F53; F55; F59; F19; 330; cooperation; economy; international relations